(untitled) (Global Journal of Science Frontier Research, 2018)
In this paper, new exact models for Einstein field equations are generated using a Van der Waals equation of state. We consider anisotropic stellar objects with no electromagnetic field distribution. Our models contain previous results as a special case. Models generalized in our performance include a familiar uncharged Einstein model with no pressure anisotropy. It is interesting that our models indicate that when matter variables vanish, gravitational potentials remain constant. This condition agrees with Minkowski spacetime. The physical features of our models show that the gravitational potentials and matter variables are well behaved. We also compute relativistic stellar masses and radii consistent with the stars PSR J1614-2230, Vela X-1, 4U 1538-52, LMC X-4, SMC X-4, Cen X-3, Her X-1, SAX J1808. 4-3658 and EXO 1785-248.